Qualitative approach to experiences of pregnant adolescents - Reyes-López, Silvia Vianey (Universidad de Sonora, 2020)
Introduction: In recent years, adolescent pregnancy has become an alarming public health problem since each year 16 million adolescents between 15 and 19 years of age become mothers. Objective: Describe experiences of pregnant teenagers, from a qualitative approach. Methodology: Qualitative, descriptive study, where nine pregnant adolescents participated, who were selected using convenience sampling. Semi-structured interviews were carried out until data saturation; the research adhered to the General Health Act for research. Results: The findings of the discourse of the adolescents were structured around three main categories: 1) factors that contribute to pregnancy with four subcategories: misuse of contraceptive methods, self-restraint to ask about contraceptive methods, unplanned sexual relations and consumption of substances; 2) reaction to the news of pregnancy with two subcategories: positive and adverse reaction; and 3) changes to pregnancy, with three subcategories: changes in school, physical and physiological changes, and changes in social behavior. Conclusions: The experiences of adolescents with respect to their pregnancy cover a range of ambivalent situations. Additionally, the experiences that a pregnant adolescent faces are multidimensional; thus, a comprehensive and multidisciplinary approach is required.